Participatory medicine: model based tools for engaging and empowering the individual - Sagar, Mark (Interface Focus, 2016)
The long-term goal of the Virtual Physiological Human and Digital Patient projects is to run 'simulations’ of health and disease processes on the virtual or 'digital' patient, and use the results to make predictions about real health and determine the best treatment specifically for an individual. This is termed 'personalized medicine', and is intended to be the future of healthcare. How will people interact and engage with their virtual selves, and how can virtual models be used to motivate people to actively participate in their own healthcare? We discuss these questions, and describe our current efforts to integrate and realistically embody psychobiological models of face-to-face interaction to enliven and increase engagement of virtual humans in healthcare. Overall, this paper highlights the need for attention to the design of human–machine interfaces to address patient engagement in healthcare.